Precision therapy for epilepsy due to KCNT1 mutations: A randomized trial of oral quinidine. (2nd January 2018) - Mullen, Saul A.; Carney, Patrick W.; Roten, Annie; Ching, Michael; Lightfoot, Paul A.; Churilov, Leonid; Nair, Umesh; Li, Melody; Berkovic, Samuel F.; Petrou, Steven; Scheffer, Ingrid E.
Abstract : Objective: To evaluate quinidine as a precision therapy for severe epilepsy due to gain of function mutations in the potassium channel gene KCNT1 . Methods: A single-center, inpatient, order-randomized, blinded, placebo-controlled, crossover trial of oral quinidine included 6 patients with severe autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) due to KCNT1 mutation. Order was block randomized and blinded. Four-day treatment blocks were used with a 2-day washout between. Dose started at 900 mg over 3 divided doses then, in subsequent participants, was reduced to 600 mg, then 300 mg. Primary outcome was seizure frequency measured on continuous video-EEG in those completing the trial. Results: Prolonged QT interval occurred in the first 2 patients at doses of 900 and 600 mg quinidine per day, respectively, despite serum quinidine levels well below the therapeutic range (0.61 and 0.51 μg/mL, reference range 1.3–5.0 μg/mL). Four patients completed treatment with 300 mg/d without adverse events. Patients completing the trial had very frequent seizures (mean 14 per day, SD 7, median 13, interquartile range 10–18). Seizures per day were nonsignificantly increased by quinidine (median 2, 95% confidence interval −1.5 to +5, p = 0.15) and no patient had a 50% seizure reduction. Conclusion: Quinidine did not show efficacy in adults and teenagers with ADNFLE. Dose-limiting cardiac side effects were observed even in the presence of low measured serum quinidine levels. Although small, this trial suggests use of quinidine in ADNFLE is likely to be ineffective coupled with considerable cardiac risks. Clinical trials registration: Australian Therapeutic Goods Administration Clinical Trial Registry (trial number 2015/0151). Classification of evidence: This study provides Class II evidence that for persons with severe epilepsy due to gain of function mutations in the potassium channel gene KCNT1, quinidine does not significantly reduce seizure frequency.